2011
DOI: 10.1111/j.1526-4637.2011.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation for Testicular Pain

Abstract: Testicular pain may be difficult to treat particularly in patients unable to tolerate opioid analgesics. In cases that have failed conservative therapy, a trial of spinal cord stimulation should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Few treatments for chronic testicular pain have been shown to achieve total pain relief. Several trials have evaluated microsurgical denervation of the spermatic cord, orchiectomy, epididymectomy, and other treatment , but there are only two other case reports of SCS for testicular pain . To our knowledge this is the first case of chronic testicular pain due to tubercular epididymitis treated successfully with SCS.…”
Section: Discussionmentioning
confidence: 91%
“…Few treatments for chronic testicular pain have been shown to achieve total pain relief. Several trials have evaluated microsurgical denervation of the spermatic cord, orchiectomy, epididymectomy, and other treatment , but there are only two other case reports of SCS for testicular pain . To our knowledge this is the first case of chronic testicular pain due to tubercular epididymitis treated successfully with SCS.…”
Section: Discussionmentioning
confidence: 91%
“…Notably, this was a much higher percentage response to spinal cord stimulation than for their overall response (56%). Other studies have shown efficacy of spinal cord stimulation in post thoracotomy pain for lung carcinoma [54], back pain related to carcinoma [55], leg pain [56,57] and groin/testicular pain [58,59]. Whilst more studies are needed, spinal cord stimulation appears to be a promising therapy for intractable cancer pain.…”
Section: Neuromodulationmentioning
confidence: 99%
“…However, after treatment many are able to return to work (Doubleday et al, 2003;McJunkin et al, 2009;Nouri & Brish, 2011;Rosendal et al, 2012).…”
Section: Social Aspectsmentioning
confidence: 99%
“…A visual analog scale is used to measure intensity. Only three of the research articles (Ciftci et al, 2011;de Oliveira et al, 2009;Misra, Ward, & Coker, 2009) and four of the case reports (McJunkin, Wuollet, & Lynch, 2009;Nouri & Brish, 2011;Rosendal, Moir, de Pennington, Green, & Aziz, 2012;Rowell & Rylander, 2012) include the quality of CTP. Sinclair, Miller, and Lee (2007) offer support for a neuropathic origin of CTP and are the first to show that neuromodulating medications decrease pain in chronic orchialgia.…”
Section: Biological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation